Clinical Insignficance of Monoclonal T-Cell Populations and Duodenal Intraepithelial T-Cell Phenotypes in Celiac and Nonceliac Patients. (February 2019) - Celli, Romulo; Hui, Pei; Triscott, Hannah; Bogardus, Sidney; Gibson, Joanna; Hwang, Michael; Robert, Marie E.
Abstract : Refractory celiac disease (RCD) is a rare condition, usually managed at specialized centers. However, gastroenterologists and pathologists in general practices are often the first to consider a diagnosis of RCD in celiac patients with persistent symptoms. The distinction between type I and type II RCD is crucial as patients with RCD II have a shortened life expectancy. The diagnosis of RCD II requires the demonstration of abnormal intraepithelial lymphocytes and/or monoclonal T-cell populations in duodenal biopsies, typically assessed in formalin-fixed paraffin-embedded tissue. We investigated the clinical significance of T-cell receptor gene rearrangements and CD3/CD8 staining in formalin-fixed paraffin-embedded biopsies from 32 patients with RCD I (4), RCD II (3), newly diagnosed celiac disease (CD) (10), established CD patients with follow-up biopsies (10), and Helicobacter pylori –associated lymphocytosis (5). Clonal T-cell populations were present in all lymphocytosis groups but not in normal controls. No difference in the frequency of clonal populations or persistence of identical clones was found between RCD I and II patients. The degree of villous blunting did not correlate with clonal status in any group. No difference in the number of CD3/CD8-positive intraepithelial lymphocytes per 100 enterocytes was found between groups. We suggest that clonal evaluation of T cells should not be employed routinely in the evaluation of CD patients with persistent symptoms until common causes of "apparent refractoriness" have been excluded. In addition, lymphocyte phenotyping and T-cell clonal analysis appear to be insufficient as stand-alone tests to reliably distinguish RCD I and II.